Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kepuasan Kerja Karyawan - Muhammad Elfi Azhar; Deissya Utami Nurdin; Yudi Siswadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this study was to determine and analyze the effect of work discipline on job satisfaction, to know and analyze the effect of compensation on job satisfaction and to find out and analyze the effect of work discipline and compensation on employee job satisfaction at PT. Mitra Abadi Setiacargo - Medan. The approach used in this research is an associative approach. The population in this study were all employees of PT. Mitra Abadi Setiacargo - Medan, amounting to 34 people using a saturated sample so that all members of the population are sampled. Data collection techniques in this study used a questionnaire technique. Data analysis techniques in this study used the Classic Assumption Test, Multiple Regression, t Test, F Test and Determination Coefficient. Partially known work discipline variables have a positive and significant influence on job satisfaction of employees of PT. Mitra Abadi Setiacargo - Medan. Partially known compensation variable has a positive and significant effect on job satisfaction of employees of PT. Mitra Abadi Setiacargo- Medan. Simultaneously it is known that work discipline and compensation have a positive and significant influence on job satisfaction of employees of PT. Mitra Abadi Setiacargo. The coefficient of determination is 0.887 or 88.7%. This shows 88.7% of the variables of work discipline and compensation contribute to job satisfaction. The remaining 11.3% is influenced by other factors not examined.